Edukasi Kesehatan Reproduksi Dalam Penanganan Dismenore Pada Remaja Kegiatan Kampung Kb Padang Bulan Kec. Medan Baru Kota Medan Tahun 2023 - Damayanty S; Ninsah Mandala Putri; Ade Rachmat Yudiyanto; Marta Armita Silaban; Ika Damayanti Sipayung; Lisa Erawati Sibarani (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Adolescence is a transitional period from childhood to adulthood, usually from 10-19 years. One of the signs of physical changes in young women will be experiencing increased hormone levels which can cause the maturation of the breasts, ovaries, uterus and vagina as well as in young women starting to experience menstruation. Menstruation begins between the ages of 12-15 years and lasts until the age of 45-50 years, one of the most common complaints felt by adolescents during menstruation is dysmenorrhea. According to WHO, this is the population at the age of 10-19 years, while according to PEMENKES RI Number 25 of 2014 adolescents are residents aged 10-18 years, according to the BKKBN unmarried adolescents aged 10-24 years. Menstrual pain (dysmenorrhea) can have an impact on activities or activities of women, especially teenagers. If a student experiences dysmenorrhea, their learning activities at school are disrupted and they do not attend school. For example, a student who experiences dysmenorrhea cannot concentrate on studying and learning motivation will decrease because of the dysmenorrhea that is felt in the teaching and learning process and sometimes there are those who ask permission to go home because they cannot stand the dysmenorrhea they feel